2021
DOI: 10.4028/www.scientific.net/ddf.410.489
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Laser Treated Thin Sample of an Amorphous-Nanocrystalline Metallic Alloy Depending on the Initial Annealing Temperature

Abstract: The ability to control the mechanical properties of metal alloys is an urgent task in materials science. For formation of certain operational properties, in most cases, it is enough to treat the working surface of the product by laser radiation. Classical processing methods are ineffective in relation to multicomponent amorphous-nanocrystalline metallic alloys. This is due to their limited use. Usually, this treatment leads to the loss of unique properties the amorphous-nanocrystalline material. Increasing cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A comprehensive approach is needed in the field of mechanical engineering, metallurgy and modern nanotechnologies for obtaining and processing materials [13][14][15][16][17][18]. The use of new alloys [6][7][8][9][10][18][19] is important not only in the design, but also in the electrical part, for example, in generators. Comparative analysis showed that due to low dynamic losses in an active three-phase voltage rectifier, the efficiency increases up to 98%, an overall dimensions of the inductive storage and output capacitors are reduced.…”
Section: 𝑀 𝐸𝑙 = 3 • 𝑘 • 𝐼 𝑝mentioning
confidence: 99%
“…A comprehensive approach is needed in the field of mechanical engineering, metallurgy and modern nanotechnologies for obtaining and processing materials [13][14][15][16][17][18]. The use of new alloys [6][7][8][9][10][18][19] is important not only in the design, but also in the electrical part, for example, in generators. Comparative analysis showed that due to low dynamic losses in an active three-phase voltage rectifier, the efficiency increases up to 98%, an overall dimensions of the inductive storage and output capacitors are reduced.…”
Section: 𝑀 𝐸𝑙 = 3 • 𝑘 • 𝐼 𝑝mentioning
confidence: 99%
“…[ 55 ] According to experimental data and computer, modeling of the laser welding of more thick sheets requires preheating. [ 56–58 ] The austenitic structure of new steels is stable not only at all testing temperatures [ 59 ] but also after thermal cycling according to the regime 400 cycles −100 to +100 °C. [ 60 ] Mechanical properties ( Table 8 ) as well as resistivity to general, pitting, and intercrystallite corrosion [ 61 ] are high for all tested steels.…”
Section: Laser Weldingmentioning
confidence: 99%